Control de activos fijos de la empresa Grusepe S.A. en Babahoyo durante el período 2020. - Párraga Gaibor, Matilde Anabella (2022)
This case study to be conducted is in the clinical laboratory Unilab S.A, in the city of Babahoyo, consists of the theme “Control of fixed assets of the company Grusepe S.A, in the city of Babahoyo in the period 2020”, the fixed assets are the godos that in the short term can be converted into liquidity and is vital for the operation of the Company which include the different inventory devices of the clinical laboratory, also the vehicle that transports the samples, patent rights, office and transport equipment, real estate, code, useful life depreciation, etc. Fixed assets are essential for both small and large businesses one of the most common problems encountered when the information has been manipulated and not recorded correctly, in the case it is done correctly, the past is known, the present is monitored and allows for future investments. The main steps in the clinical laboratory Unilab S.A, needs to evaluate the planning of its assets and policies that ir maintains especially the needs they have. The excellent control of Fixed Assets will allow the company recognize in what state is the objects owned by the Company, if the Company does not know the useful life of and object runs the risk of los sor deterioration of the equipment in Unilab.S.A. By complying with an excellent control of fixed Assets in Unilab S.A will allow existing strategies to make decisions for investments recognition of useful life, responsible and trained personnel, location and value of each asset, periods of maintenance and movement of transfers.